PEMULIHAN ASET NEGARA MELALUI GUGATAN PERDATA DAN TAHAPAN PENGEMBALIAN ASET HASIL TINDAK PIDANA KORUPSI (Suatu Terobosan Konstruktif dalam Penegakan Hukum yang Progresif) (Solusi, 2023)
Law The efforts of the State Attorney in connection with the return of state finances due to corruption crimes by conducting civil suits, on the other hand, civil suits are filed after criminal acts are no longer possible, because they are faced with certain conditions as referred to in Articles 32, 33, 34, 38C of Law Number 31 of 1999 concerning Eradication of Corruption Crimes as amended by Law Number 20 of 2001. Without the regulation in the Corruption Eradication Law, it is not possible to file a civil lawsuit. Civil suits under Article 33 and Article 34 thus require two things: 1. the suspect or defendant dies during the investigation process or court hearing, 2. there has been a real loss of state finances. The provisions of Articles 33 and 34 of the GCPL Law indicate that in any way state financial losses must be recovered even if the suspect or defendant dies. Such conditions make the lawsuit can be addressed to his heirs. Such conditions make the lawsuit can be addressed to his heirs. The GCPL Law explicitly, in addition to including material requirements in the form of state financial losses and unlawful acts, also determines formal requirements. The formal requirements in a civil lawsuit relate to the position of the state as the plaintiff. The government in order to organize welfare, protection of its citizens has the right to file a civil lawsuit to the court (Legal Standing of the Government). The action to return assets resulting from corruption is carried out in 4 (four) stages: the asset tracking stage, the freezing or return of assets stage, the confiscation of assets stage and the last stage is the handover of assets resulting from corruption to the victim or the victim's country.